Bankruptcy and Corporate Governance: The Impact of Board Composition and Structure - Daily, Catherine M.; Dalton, Dan R. (Academy of Management Journal, 1994)
In this study, we examined the relationships among governance structures and corporate bankruptcy. A logistic regression analysis of bankrupt major corporations and a matched group of survivor firms indicated robust power for financial indicators, constituent common stock holdings, board of director quality, and corporate governance structures as predictors of bankruptcy. Specifically, the model indicates differences between the bankrupt and matched groups in proportions of affiliated directors, chief executives, board chairperson structure, and their interaction.